The Relationships between Selected Factors and Postoperative Pain among Patients Undergone General Anesthesia in Recovery Room - Prommala, Patcharee; Prommala, Patcharee; Toskulkao, Tipa; Changmai, Sakul (Nursing Journal of The Ministry of Public Health, 2023)
This retrospective descriptive correlational study aimed to investigate the relationships between selected factors and postoperative pain among patients undergoing general anesthesia in recovery room. Retrospective data were collected from the review of medical records between January 2019 to December 2021. The proportion of the sample was determined based on the total number of patients per year. Stratified simple random sampling was performed on an eligible sample of 112 patients who met the criteria. The research instruments included personal data record forms, a surgical record and post anesthesia record. The data were analyzed using descriptive statistics and Chi-square tests. The results showed that most of the samples received pain management (79.5%), had pain experience (50.9%), had undergone general surgery (49.1%), and had no complications (83.0%). Pain management and the number of complications were correlated with postoperative pain at the statistically significant level of p<.05 (χ2=77.554, p= .000, χ2=14.445, p=.000, respectively). However, experience of pain and type of surgery were not correlated with postoperative pain. Healthcare providers should pay more attention to postoperative pain management to improve the quality of care provided to patients in the recovery room after surgery.